LITERACY AND SOCIAL MOBILITY IN CHIMAMANDA NGOZIE ADICHIE’S THE HALF OF A YELLOW SUN - Rizky Nur Octavia Maharani Sudarmono (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Literacy is one of the important skills in order to survive in the society. Having high literacy skills means having a big opportunity to has a good status in the public. With the help of education, it is possible to achieve that. However, there are some conditions that it is difficult to access, such as a war. This kind of situation is nicely depicted in Chimamanda Ngozi Adichie’s The Half of a Yellow Sun. Thus, this study is conducted to analyze how literacy practices could affect the social status in a society in The Half of a Yellow Sun. This research emphasizes into two problems (1) how the social mobility is depicted in the story and (2) how the concept of social mobility shaped by literacy practice that the characters experienced. This study employs Pitirim A. Sorokin’s theory of social mobility in order to elaborate how literacy skills could affect status in the society. The result shows that there are two types of social mobility that portrayed in the story. The first type is horizontal social mobility. The second is vertical social mobility, there are two types of it which are social climbing and social sinking. Finally, literacy is the main reason of this social mobility shifting. Keywords: Literacy, social mobility